Assessment of drought impacts on vegetation health: a case study in Kedah - Othman, M.; Ash’aari, Z. H.; Muharam, F. M.; Sulaiman, W. N. A.; Hamisan, H.; Mohamad, N. D.; Othman, N. H. (IOP Publishing, 2016)
Prolonged drought in the early of 2014 has caused Malaysia to experience water supply shortage which directly affects both health and growth of vegetation. Thus this study aims to assess the risk vegetation areas that were impacted during 2014's drought by integrating the Standardized Precipitation Index (SPI) and Normalized Differentiation Vegetation Index (NDVI) methods. These two methods were able to assess the risk areas for the vegetation by measuring its health and classifying them according to its severity while considering the rainfall reduction at the specific time and location. The results obtained from this study shows that the central and north west of Kedah was vulnerable to the occurrence of drought. Kedah was more impacted by the dry event during the northeast monsoon. This study is significant as a fundamental input for further research and as an alternative approach by the application of space technology.